THE EFFECT OF EXPERIENTIAL MARKETING AND CUSTOMER EXPERIENCE ON REVISIT INTENTION WITH PERCEIVED VALUE AS A MEDIATION VARIABLE IN THE VILLA INDUSTRY IN BALI PROVINCE - Anak Agung Ngurah Manik Indra Putra; Desak Made Febri Purnama Sari; Anak Agung Ayu Mirah Kencanawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The villa industry in Bali Province faces increasingly fierce competition due to the increasing number of accommodations, changing tourist preferences, and growing demands for authentic and sustainable tourism experiences. This condition is exacerbated by the declining occupancy rate of legal villas in Bali, necessitating strategies capable of increasing tourist loyalty through revisit intention . In this context, experiential marketing and customer experience are seen as important factors that can shape sustainable perceived value and encourage tourist revisit intentions. This study aims to analyze the influence of experiential marketing and customer experience on revisit intention through sustainable perceived value in the villa industry in Bali Province. This study uses a quantitative approach with a survey method of tourists who have stayed at villas in Badung, Gianyar, and Tabanan Regencies. Data collection was carried out by distributing structured questionnaires to respondents, namely foreign and local tourists who meet the research criteria. The research data were analyzed using inferential statistics to test the direct and indirect effects between research variables, including experiential marketing, customer experience, sustainable perceived value, and revisit intention. The results show that experiential marketing and customer experience have a positive and significant effect on sustainable perceived value among customers of the villa industry in Bali. Furthermore, sustainable perceived value has been shown to have a positive and significant effect on revisit intention. This study also found that experiential marketing and customer experience have a positive and significant effect on revisit intention, both directly and indirectly through sustainable perceived value as a mediating variable. These findings indicate that an authentic, comfortable, and memorable customer experience can increase tourists' perceived value towards the villa, thereby encouraging tourists' intention to revisit. This study provides theoretical contributions to the development of experiential marketing, customer experience , and consumer behavior studies in the sustainable tourism sector. Furthermore, this study also provides practical implications for villa managers in Bali to design marketing strategies oriented towards customer experience, service quality, and sustainable value creation to increase tourist loyalty and revisit intention amidst the increasingly competitive villa industry.